2008
DOI: 10.2134/agronj2008.0016
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll Measurements and Nitrogen Nutrition Index for the Evaluation of Corn Nitrogen Status

Abstract: Plant-based diagnostic techniques are used to determine the level of crop N nutrition but there is limited comparative research on the diff erent methods. Our objectives were to establish the relationship between chlorophyll meter (CM) readings and N nutrition index (NNI) during the corn (Zea mays L.) growing season, and to compare both methods as diagnostic tools for predicting grain yield response to N fertilization. Th e study was established at eight site-years using four to seven N fertilization rates. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
111
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(133 citation statements)
references
References 51 publications
(122 reference statements)
18
111
3
1
Order By: Relevance
“…NNI was positively related to SPAD values. The increase in NNI with increasing N fertilization has been previously reported in corn (Plénet and Cruz, 1997;Ziadi et al, 2008) and in wheat (Debaeke et al, 2006;Prost and Jeuffroy, 2007). This positive relationship varied across different developmental stages and leaf positions.…”
Section: Correlation Of Spad and Rspad Values With Nni Atsupporting
confidence: 71%
See 1 more Smart Citation
“…NNI was positively related to SPAD values. The increase in NNI with increasing N fertilization has been previously reported in corn (Plénet and Cruz, 1997;Ziadi et al, 2008) and in wheat (Debaeke et al, 2006;Prost and Jeuffroy, 2007). This positive relationship varied across different developmental stages and leaf positions.…”
Section: Correlation Of Spad and Rspad Values With Nni Atsupporting
confidence: 71%
“…The non-linear relationship between SPAD values and NNI has been proved in fescue (Errecart et al, 2012), corn (Ziadi et al, 2008), wheat (Vouillot et al, 1998;Prost and Jeuffroy, 2007) and cocksfoot (Duru, 2002), and the correlation of RSPAD values with NNI, and relative grain yield has been studied only in corn (Ziadi et al, 2008) and wheat (Debaeke et al, 2006). Debaeke et al (2006) also found that the non-linear relationship between RSPAD values and NNI was not significantly affected by years, genotypes, and developmental stages.…”
mentioning
confidence: 99%
“…The NNI was also shown to be a reliable predictor of corn relative yield (Ziadi et al 2008b). Weed interference had a relatively small affect on soil NO 3 -N, but a relatively large affect on NNI, primarily as the result of the large influence of weed interference on corn growth.…”
Section: Resultsmentioning
confidence: 94%
“…A simple nondestructive diagnostic tool would be considerably more convenient for practitioners. Several authors have shown that measured NNI was highly correlated to the normalized index obtained from measurements made with the SPAD 502 chlorophyll meter, which provides a rapid, nondestructive estimate of relative leaf chlorophyll content (Debaeke et al 2006;Ziadi et al 2008b). If the SPAD meter can be used to predict NNI reliably, it may also be a useful tool for assessing the relative impact of weeds on crops.…”
mentioning
confidence: 99%
“…Leaf chlorophyll content was assessed in the current experiment as a non-destructive method for the N status in plant shoots (Byju & Anand 2009). Ziadi et al (2008) reported that the relationship between chlorophyll meter readings and N nutrition index was stable across site and years, and could be used to detect and quantify N deficiencies in maize. In the current study, significant relationships were established between chlorophyll readings and shoot weight, soil-exchangeable Al% and pH values 35 days after sowing (Table 6).…”
Section: Discussionmentioning
confidence: 99%